Characteristics of Passive Films Formed on As-Cast Ti–6Al-4V in Hank’s Solution Before and After Transpassivation - Yi, Guo; Liu, Xinxin; Zheng, Chuanbo; Zhang, Hongyue; Xu, Cheng; Cui, Yu-Wei; Liu, Shuan (Frontiers in Materials, 2021)
In this work, the characteristics of passive films formed on as-cast Ti-6Al-4V before and after transpassivation by electrochemical methods will be studied. A simulated body fluid of Hank’s solution was used as the electrolyte in this work. According to the potentiodynamic polarization test, the passivation range, transpassive range, and repassivation range of as-cast Ti-6Al-4V were obtained. Afterward, the potentiostatic polarization was employed to passivate the Ti-6Al-4V in both passivation and repassivation ranges. Electrochemical impedance spectroscopy (EIS) was used to analyze the characteristics of formed passive films. Different electrochemical behavior of as-cast Ti–6Al-4V is found in passivation and repassivation ranges. The passivation current density of the sample in the repassivation range is significantly larger than that in the passivation range. Meanwhile, the growth rate of passive film in the repassivation range is also greater than that in the passivation range. Although the sample shows a higher charge transfer impedance in the repassivation range, metastable pitting corrosion is also observed, indicating the formation of the unstable passive film. Such results advance the understanding of as-cast Ti-6Al-4V polarized under different potentials for potential biomedical applications.